HUBUNGAN USIA IBU DENGAN TINDAKAN SECTIO CAESARIAN DI RSUD DR SAM RATULANGI TONDANO - Yunita Waney, Jein; Sri Purwanti, Anik (NHM PRESS, 2024)
Background: The increasing incidence of caesarean section (SC) among mothers giving birth has become a global concern in the field of reproductive health. Maternal age has been identified as a potential risk factor influencing the propensity to undergo CS. However, research on the relationship between maternal age and SC procedures is still not widespread, especially in the Dr. Sam Ratulangi Tondano. Objective: This study aims to explore the relationship between maternal age and the tendency to undergo caesarean section at RSUD Dr. Sam Ratulangi Tondano. Method: This study used a retrospective research design by collecting data from 24 mothers who underwent CS procedures at RSUD Dr. Sam Ratulangi Tondano. Data on maternal age at delivery and type of delivery (SC or normal) were collected from medical records and analyzed using appropriate statistical tests. Results: Data analysis showed that of the 24 samples studied, there was significant variation in the incidence of CS based on maternal age. The results of statistical tests show that maternal age has a significant effect on the tendency to undergo CS (p < 0.05), with a higher prevalence occurring in mothers of a certain age. Conclusion: This research confirms the existence of a significant relationship between maternal age and the tendency to undergo caesarean section at Dr. Sam Ratulangi Tondano. These results emphasize the importance of monitoring maternal age as a determining factor in medical decisions regarding mode of delivery. It is hoped that increased understanding of these risk factors will assist in more effective birth planning and management, with the ultimate goal of improving maternal and neonatal health outcomes in the region.